2014
DOI: 10.22495/rgcv4i3c1art2
|View full text |Cite
|
Sign up to set email alerts
|

Task performance fraud risk assessment on forensic accountant and auditor knowledge and mindset in Nigerian public sector

Abstract: This paper discusses task performance fraud risk assessment and forensic accountant and auditor knowledge and mindset in the Nigerian public sector. The aim of the study is to examine the fraud risk assessment in the Nigerian public sector through the efficient utilisation of forensic accountant and auditor knowledge and mindset.The effect will enhance the corporate governance and accountability practices among public sector accountants and auditors in Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Mindset is the positive mental attitude of a forensic accountant and auditor to prevent, detect and response to fraud (Popoola et al, 2013b;Wuerges, 2011;Chui, 2010;Singleton & Singleton, 2007). Hypothesis H2 of this study states that Mindset -forensic accountant and auditor (MR) is positively related to task performance fraud risk assessment (TPFRA).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Mindset is the positive mental attitude of a forensic accountant and auditor to prevent, detect and response to fraud (Popoola et al, 2013b;Wuerges, 2011;Chui, 2010;Singleton & Singleton, 2007). Hypothesis H2 of this study states that Mindset -forensic accountant and auditor (MR) is positively related to task performance fraud risk assessment (TPFRA).…”
Section: Discussionmentioning
confidence: 94%
“…Knowledge in this study refers to the forensic accountant and the auditor's attribute and proficiency competences necessary and relevant to discharge technical and innovative task, especially with respect to identifying and analysing methods and procedures for fraud prevention, detection and response from the Nigerian public sector environment (Popoola et al, 2013a;Popoola et al, 2013b;Davis, Farrell & Ogilby, 2010;Ramaswamy, 2007;. Hypothesis H1 of this study states that Knowledge -forensic accountant and auditor (KR) is positively related to task performance fraud risk assessment (TPFRA).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Without proper and adequate forensic education, expecting financial statement auditors to detect fraud is similar to pouring new wine into old bottles (Wuerges, 2011 AICPA, 2002) These standards contain recommendation that the "auditor may respond to an identified risk of material misstatement due to fraud by assigning the forensic or IT specialists" (Popoola et al, 2013b;Chui, 2010;AICPA, 2002). Davia (2000) found that fraud detection is distinct from the financial statement audit, and it requires a diverse knowledge area, which can only be carried out through forensic accounting techniques.…”
Section: Forensic Accountants and Auditors Knowledge Requirementmentioning
confidence: 99%